2011
DOI: 10.1101/gr.110528.110
|View full text |Cite
|
Sign up to set email alerts
|

Reading TE leaves: New approaches to the identification of transposable element insertions

Abstract: Transposable elements (TEs) are a tremendous source of genome instability and genetic variation. Of particular interest to investigators of human biology and human evolution are retrotransposon insertions that are recent and/or polymorphic in the human population. As a consequence, the ability to assay large numbers of polymorphic TEs in a given genome is valuable. Five recent manuscripts each propose methods to scan whole human genomes to identify, map, and, in some cases, genotype polymorphic retrotransposon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
71
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(74 citation statements)
references
References 126 publications
2
71
0
1
Order By: Relevance
“…We included a Rescorla-Wagner (RW) model [13] which in our paradigm makes similar predictions as a more general temporal difference rule [32]. A hybrid RW-Pearce-Hall model (HM) [33] which has been used to specifically explain SCR in threat learning, and augments the RW model with a notion of associability [14].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We included a Rescorla-Wagner (RW) model [13] which in our paradigm makes similar predictions as a more general temporal difference rule [32]. A hybrid RW-Pearce-Hall model (HM) [33] which has been used to specifically explain SCR in threat learning, and augments the RW model with a notion of associability [14].…”
Section: Resultsmentioning
confidence: 99%
“…The RW model [13] specifies that US prediction ('associative strength') is updated according to a signed prediction error signal (i.e. the difference between the prediction on a given trial, x t and the observed sensory input, u t ), weighted by a fixed learning rate, η which is a subject-specific free parameter across both CS, such that such that 0< η <1: …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of their deleterious effects, TE insertions are expected to be under purifying selection (Hollister and Gaut 2009), leading to lower levels of TEs in selfers compared with outcrossers (Morgan 2001;Lockton and Gaut 2010). Moreover, the mating system in plants has been shown to influence TE accumulation and distribution (Morgan 2001;Lockton and Gaut 2010), and there is evidence that genome size variability is influenced by TEs (Bennetzen et al 2005;Ray and Batzer 2011). In apomicts, TE accumulation has been implicated in the evolution of genomic regions that harbor apomixis factors (Akiyama et al 2004;Okada et al 2011) and is hypothesized to be a factor that contributes to eventual lineage extinction (Dolgin and Charlesworth 2006).…”
Section: Genomic Parasite Frequencies Reflect Both Phylogenetic Histomentioning
confidence: 99%
“…Future studies shall focus on quantifying the level of piggyBat transposase expression in different bat tissues and examining whether host defense pathways known to repress retroelements in some mammals (e.g., small RNAs, DNA methylation) are operating to control piggyBat transposition. The recent development of high-throughput technologies to display and capture recent and de novo transposition events, both somatic and germ line, in organisms (38,39) should be readily applicable to estimate the frequency of piggyBat transposition in natural populations and to assess the amount of structural genomic variation mediated by recent and likely ongoing piggyBat activity.…”
mentioning
confidence: 99%